Were Oil Price Markets the Source of Credit Crisis in European Countries? Evidence Using a VAR-MGARCH-DCC Model - Selmi, Nadhem; Hachicha, Nejib (International Journal of Energy Economics and Policy, 2014)
This paper examines the role of oil prices, credit, financial and commercial linkages in the propagation of industrial market crises during the period 2004-2012. Using VAR-MGARCH-DCC model regressions on seven markets finds that credit linkage played a significant role in the subprime, financial and global crises. Our results also show that the European debt crisis has already spread like a crisis from oil prices to Ireland and Portugal, and other countries are now at risk: Spain is a probable candidate for financial crisis. Keywords: Oil price; Contagion; Crisis; VAR-MGARCH-DCC. JEL Classifications: C32; C52